2018
DOI: 10.1113/ep087065
|View full text |Cite
|
Sign up to set email alerts
|

Thirty minutes of handgrip exercise potentiates flow‐mediated dilatation in response to sustained and transient shear stress stimuli to a similar extent

Abstract: Brief (30 min) exposure of the brachial artery (BA) to a sustained elevation in shear stress has been shown to potentiate subsequent BA flow-mediated dilatation (FMD) in response to a transient shear stress stimulus [reactive hyperaemia (RH) FMD]. It is unknown whether matching the sustained shear stress exposure to a subsequent sustained shear stress stimulus for FMD [via handgrip exercise (SS-FMD)] might enhance the potentiation of FMD. The purpose of the study, therefore, was to assess the impact of a 30 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…shear stress mediated (1,18,32). For example, McPhee and Pyke (18) suggested that handgrip exercise resulted in similar vasodilation-induced by reactive hyperemia (FMD) and sustained shear (HE).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…shear stress mediated (1,18,32). For example, McPhee and Pyke (18) suggested that handgrip exercise resulted in similar vasodilation-induced by reactive hyperemia (FMD) and sustained shear (HE).…”
Section: Discussionmentioning
confidence: 99%
“…shear stress mediated (1,18,32). For example, McPhee and Pyke (18) suggested that handgrip exercise resulted in similar vasodilation-induced by reactive hyperemia (FMD) and sustained shear (HE). In contrast, there are other studies suggesting that vasodilation in response to reactive and active hyperemia may be driven by distinct mechanisms (25).…”
Section: Discussionmentioning
confidence: 99%
“…Basal leg blood flow can be affected by numerous common stimuli including exercise, mental stress, arousal and a variety of environmental factors (McPhee & Pyke, 2018; Pearson et al., 2011; Sarabi & Lind, 2001; Tinken et al., 2009; Venturelli et al., 2012). In this investigation, cutaneous heating was employed as a means of experimentally manipulating baseline blood flow prior to the assessment of PLM‐induced hyperaemia.…”
Section: Discussionmentioning
confidence: 99%
“…As shear stress is a primary stimulus in the PLM blood flow response, the magnitude of baseline blood flow may play an important role in the subsequent stimulus response. Of note, baseline leg blood flow, and therefore shear stress, can be affected by many common conditions, including prior exercise, level of arousal and numerous environmental factors (McPhee & Pyke, 2018; Pearson et al., 2011; Tinken et al., 2009; Venturelli et al., 2012). However, studies aiming to pre‐expose the vasculature to increased shear stress, in order to examine the effect on NO‐mediated vasodilation, have produced conflicting results (Doshi et al., 2001; Green et al., 2014; Joannides et al., 1995; Kooijman et al., 2008; Sarabi & Lind, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation